Genome Sequence of the Polycyclic Aromatic Hydrocarbon-Degrading Bacterium Strain Marinobacter nanhaiticus D15-8W(T) - Cui, Zhisong (American Society for Microbiology, 2013)
Marinobacter nanhaiticus strain D15-8W(T) was isolated from a phenanthrene-degrading consortium, enriched from sediment of the South China Sea. Here, we present the draft genome of strain D15-8W(T), which contains 5,358,309 bp with a G+C content of 58.53% and contains 4,829 protein-coding genes and 47 tRNA genes.